Job Creation Law and Foreign Direct Investment in Tourism in Indonesia: Is It Better than Before? - I Gusti Ngurah Parikesit Widiatedja; I Nyoman Suyatna (Udayana Journal of Law and Culture, 2022)
Foreign direct investment plays a critical role in a host country's economic development. Tourism, with its distinct character as a service business, is one of the most appealing investment industries. It has made a substantial contribution to the creation of jobs, tax revenue, and domestic value-added. The existence of domestic laws and regulations is critical in determining the extent to which a country's performance in getting benefits from investment can be maximized while reducing the negative impact. This article is aimed to examine whether the newly-enacted Job Creation Law provides a better arrangement on foreign direct investment in tourism compared to the previous laws and regulations. This article employs a normative approach by analyzing relevant laws and regulations concerning foreign direct investment in tourism in Indonesia. By looking at aspects on the choice of business fields, the issuance of business permit, land ownership, and labour, this article contends that Job Creation Law fails to provide integrated and comprehensive arrangements on the existence of foreign direct investment in tourism.